Two mRNA-Binding Proteins Regulate the Distribution of Syntaxin mRNA in Aplysia Sensory Neurons - Liu, Jinming (J Neurosci, 2006)
Targeting mRNAs to different functional domains within neurons is crucial to memory storage. In Aplysia sensory neurons, syntaxin mRNA accumulates at the axon hillock during long-term facilitation of sensory-motor neuron synapses produced by serotonin (5-HT). We find that the 3′ untranslated region of Aplysia syntaxin mRNA has two targeting elements, the cytosolic polyadenylation element (CPE) and stem-loop double-stranded structures that appear to interact with mRNA-binding proteins CPEB and Staufen. Blocking the interaction between these targeting elements and their RNA-binding proteins abolished both accumulation at the axon hillock and long-term facilitation. CPEB, which we previously have shown to be upregulated after stimulation with 5-HT, is required for the relocalization of syntaxin mRNA to the axon hillock from the opposite pole in the cell body of the sensory neuron during long-term facilitation, whereas Staufen is required for maintaining the accumulation of the mRNA both at the axon hillock after the treatment with 5-HT and at the opposite pole in stable, unstimulated sensory neurons. Thus, the cooperative actions of the two mRNA-binding proteins serve to direct the distribution of an mRNA encoding a key synaptic protein.